Chapter 11 Calculation of Derivatives

Chapter 11 Calculation of Derivatives

Chapter 11 Calculation of Derivatives 11.1 Derivatives of Some Special Functions 11.1 Theorem (Derivative of power functions.) Let r ∈ Q and let f(x) = xr. Here 8 > R if r ∈ Z > ≥0 < R \{0} if r ∈ Z− domain(f) = > + > R≥0 if r ∈ Q \ Z : R+ if r ∈ Q− \ Z. Let a be an interior point of domain(f). Then f is differentiable at a, and f 0(a) = rar−1. If r = 0 and a = 0 we interpret rar−1 to be 0. Proof: First consider the case a 6= 0. For all x in domain(f) \{a} we have ³ ´ ³ ´ f(x) − f(a) xr − ar ar ( x )r − 1 ( x )r − 1 = = ³ a ´ = ar−1 a . x − a x − a x ( x − 1) a ( a ) − 1 a Let {xn} be a generic sequence in domain(f) \{a} such that {xn} → a. Let n r o xn yn − 1 yn = . Then {yn} → 1 and hence by theorem 7.10 we have → r a yn − 1 and hence ( ) ( ) f(x ) − f(a) yr − 1 n = n · ar−1 → rar−1. xn − a yn − 1 237 238 CHAPTER 11. CALCULATION OF DERIVATIVES This proves the theorem in the case a 6= 0. If a = 0 then r ∈ Z≥0 (since for other values of r, 0 is not an interior point of domain(f)). In this case ½ f(x) − f(0) xr − 0r 0 if r = 0 (remember 00 = 1). = = x − 0 x xr−1 if r 6= 0. Hence 8 f(x) − f(0) < 0 if r = 0, f 0(0) = lim = 1 if r = 1, x→0 x : 0 if r > 1. Thus in all cases the formula f 0(x) = rxr−1 holds. ||| 11.2 Corollary (Of the proof of theorem 11.1) For all r ∈ Q, xr − 1 lim = r. x→1 x − 1 11.3 Theorem (Derivatives of sin and cos.) Let r ∈ R and let f(x) = sin(rx), g(x) = cos(rx) for all x ∈ R. Then f and g are differentiable on R, and for all x ∈ R f 0(x) = r cos(rx), (11.4) g0(x) = −r sin(rx). (11.5) Proof: If r = 0 the result is clear, so we assume r 6= 0. For all x ∈ R and all t ∈ R \{x}, we have ³ ´ ³ ´ r(t+x) r(t−x) sin(rt) − sin(rx) 2 cos sin = 2 2 t − x t − x ³ ´ r(t−x) ³r(t + x)´ sin = r cos · ³ 2 ´ . 2 r(t−x) 2 (Here I’ve used an identity from theorem 9.21.) Let {xn} be a generic sequence r(x + x) r(x − x) in R \{x} such that {x } → x. Let y = n and let z = n . n n 2 n 2 Then {yn} → rx so by lemma 9.34 we have {cos(yn)} → cos(rx). Also n o + sin(zn) {zn} → 0, and zn ∈ R \{0} for all n ∈ Z , so by (9.38), → 1. zn Hence n o n o sin(rxn) − sin(rx) sin(zn) = r cos(yn) · → r cos(rx), xn − x zn 11.1. DERIVATIVES OF SOME SPECIAL FUNCTIONS 239 and this proves formula (11.4). ||| The proof of (11.5) is similar. 11.6 Exercise. Prove that if g(x) = cos(rx), then g0(x) = −r sin(rx). 11.7 Theorem (Derivative of the logarithm.) The logarithm function is differentiable on R+, and 1 ln0(x) = for all x ∈ R+. x Proof: Let x ∈ R+, and let s ∈ R+ \{x}. Then Z s h i ln(s) − ln(x) 1 1 1 s 1 = dt = Ax . s − x s − x x t s − x t h1i Case 1: If s > x then As represents the area of the shaded region S in the x t figure. 1 (x, x ) 1 (s, s ) S x s We have 1 1 B(x, s: 0, ) ⊂ S ⊂ B(x, s: 0, ) s x so by monotonicity of area s − x h1i s − x ≤ As ≤ . s x t x Thus 1 1 Z s 1 1 ≤ dt ≤ . (11.8) s s − x x t x Case 2. If s < x we can reverse the roles of s and x in equation (11.8) to get 1 1 Z x 1 1 ≤ dt ≤ x x − s s t s 240 CHAPTER 11. CALCULATION OF DERIVATIVES or 1 1 Z s 1 1 ≤ dt ≤ . x s − x x t s In both cases it follows that ¯ Z ¯ ¯ ¯ ¯ 1 s 1 1 ¯ ¯1 1 ¯ 0 ≤ ¯ dt − ¯ ≤ ¯ − ¯. s − x x t x s x + Let {xn} be a generic sequence in R \{x} such that {xn} → x. Then n 1 1 o − → 0 , so by the squeezing rule xn x ½ Z ¾ 1 xn 1 1 dt − → 0, xn − x x t x i.e. ( ) ln(x ) − ln(x) 1 n − → 0. xn − x x Hence nln(x ) − ln(x)o 1 n → . xn − x x 1 We have proved that ln0(x) = . ||| x 11.9 Assumption (Localization rule for derivatives.) Let f, g be two real valued functions. Suppose there is some ² ∈ R+ and a ∈ R such that (a − ², a + ²) ⊂ domain(f) ∩ domain(g) and such that f(x) = g(x) for all x ∈ (a − ², a + ²). If f is differentiable at a, then g is differentiable at a and g0(a) = f 0(a). This is another assumption that is really a theorem, i.e. it can be proved. Intuitively this assumption is very plausible. It says that if two functions agree on an entire interval centered at a, then their graphs have the same tangents at a. 11.10 Theorem (Derivative of absolute value.) Let f(x) = |x| for all x x ∈ R. Then f 0(x) = for all x ∈ R \{0} and f 0(0) is not defined. |x| 11.1. DERIVATIVES OF SOME SPECIAL FUNCTIONS 241 Proof: Since ½ x if x > 0, f(x) = −x if x < 0, it follows from the localization theorem that ( x 0 1 = |x| if x > 0, f (x) = x −1 = |x| if x < 0. To see that f is not differentable at 0, we want to show that f(t) − f(0) |t| lim = lim t→0 t − 0 t→0 t ¯ ¯ ¯ (−1)n ¯ n ¯ ¯ (−1) |xn| n n does not exist. Let xn = . Then {xn} → 0, but = (−1)n = (−1) n xn n f(t) − f(0) and we know that lim{(−1)n} does not exist. Hence lim does not t − 0 exist, i.e., f is not differentiable at 0. d 11.11 Definition ( notation for derivatives.) An alternate notation dx for representing derivatives is: d f(x) = f 0(x) dx or df = f 0(x). dx This notation is used in the following way d ³ ´ sin(6x) = 6 cos(6x), dx d ³ t ´ 1 t cos( ) = − sin( ). dt 3 3 3 Or: df 1 Let f = x1/2. Then = x−1/2. dx 2 1 dg d ³ ´ d ³ 1 ´ 1 Let g(x) = . Then = g(x) = = − . x dx dx dx x x2 d The notation is due to Leibnitz, and is older than our concept of func- dx tion. 242 CHAPTER 11. CALCULATION OF DERIVATIVES Leibnitz wrote the differentiation formulas as “dxa = axa−1dx,” or if y = xa, then “dy = axa−1dx.” The notation f 0(x) for derivatives is due to Joseph Louis Lagrange (1736-1813). Lagrange called f 0(x) the derived func- tion of f(x) and it is from this that we get our word derivative. Leibnitz called derivatives, differentials and Newton called them fluxions. Many of the early users of the calculus thought of the derivative as the quotient of two numbers df difference in f f(x) − f(t) = = dx difference in x x − t when dx = x − t was “infinitely small”. Today “infinitely small” real numbers are out of fashion, but some attempts are being made to bring them back. Cf Surreal Numbers : How two ex-students turned on to pure mathematics and found total happiness : a mathematical novelette, by D. E. Knuth.[30]. or The Hyperreal Line by H. Jerome Keisler[28, pp 207-237]. 11.2 Some General Differentiation Theorems. 11.12 Theorem (Sum rule for derivatives.) Let f, g be real valued func- tions with domain(f) ⊂ R and domain(g) ⊂ R, and let c ∈ R. Suppose f and g are differentiable at a. Then f + g, f − g and cf are differentiable at a, and (f + g)0(a) = f 0(a) + g0(a) (f − g)0(a) = f 0(a) − g0(a) (cf)0(a) = c · f 0(a). Proof: We will prove only the first statement. The proofs of the other state- ments are similar. For all x ∈ dom(f) we have (f + g)(x) − (f + g)(a) f(x) + g(x) − (f(a) + g(a)) = x − a x − a f(x) − f(a) g(x) − g(a) = + x − a x − a By the sum rule for limits of functions, it follows that à ! à ! à ! (f + g)(x) − (f + g)(a) f(x) − f(a) g(x) − g(a) lim = lim + lim , x→a x − a x→a x − a x→a x − a 11.2. SOME GENERAL DIFFERENTIATION THEOREMS. 243 i.e. (f + g)0(a) = f 0(a) + g0(a). ||| 11.13 Examples. If 1 √ f(x) = 27x3 + + 8x, 3x then 1 √ f(x) = 27x3 + x−1 + 8 · x1/2, 3 so 1 √ 1 f 0(x) = 27 · (3x2) + (−1 · x−2) + 8 · ( x−1/2) 3 s 2 1 2 = 81x2 − + . 3x2 x If g(x) = (3x2 + 7)2, then g(x) = 9x4 + 42x2 + 49, so g0(x) = 9 · 4x3 + 42 · 2x = 36x3 + 84x.

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    19 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us